Social-Based Management of Nonformal Education Programs: A Narrative Review of Participatory Governance and Community Empowerment - Alberthina Abetsi Haumahu (FKIP, Universitas Palangka Raya, 2026)
The management of nonformal education programs increasingly demands socially grounded approaches capable of fostering inclusivity, sustainability, and community empowerment. This study aims to analyze the concept and implementation of social-based management within nonformal education systems, emphasizing participatory governance, social capital, and collaborative learning as strategic components of effective program administration. Employing a qualitative narrative review methodology, this research synthesizes empirical and conceptual findings from peer-reviewed studies published between 2018 and 2025 to identify dominant themes, theoretical orientations, and emerging innovations in the field. The results reveal that social-based management strengthens institutional accountability,enhances program sustainability, and promotes shared ownership among community stakeholders. The integration of participatory management and social capital theories provides a conceptual foundation for improving nonformal education governance through collaboration, trust networks, and local knowledge mobilization. The study contributes theoretically by refining the framework of participatory educational management, and practically by offering guidance for policymakers and practitioners in designing community-driven education programs. These findings underscore the importance of socially embedded governance as a pathway toward inclusive, adaptive, and transformative nonformal education.